Pengaruh Tarif Pajak dan Pengetahuan Wajib Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Bandar Lampung (Studi pada Kantor Samsat Rajabasa Bandar Lampung) - Putri, Geo Vany Edy; Rizal, Syamsu (Jurnal EMT KITA, 2023)
Motor vehicle tax (PKB) is a form of tax levied on the ownership and/or ownership of motor vehicles, with natural or legal persons as owners of the vehicles being tax payers.  Tax awareness becomes important when taxpayers have enough knowledge and understanding of the tax system. This encourages them to voluntarily fulfill their tax payment obligations. The higher a taxpayer's level of tax awareness, the higher their level of tax compliance, while also reinforcing their role as a good citizen.  This study aims to determine the influence of tax rates and taxpayer knowledge on the compliance level of automobile taxpayers in Bandar Lampung City. The research method used was quantitative research in the tax-paying population of Bandar Lampung City. A sample of 100 respondents was selected using purposive sampling with calculations using the Slovin formula. Data was collected through document review, documentation, observations, interviews, and questionnaires. Data analysis included several linear regression tests, correlation coefficient tests, t-tests, F-tests, and R2 tests.  The study results showed that tax rate and taxpayer knowledge had a significant influence of 47.5% on vehicle tax payment compliance of taxpayers at Samsat office in Bandar Lampung Rajabasa. At the same time, other factors not considered in this study also affect 52.5% of taxpayer compliance. This study highlights the importance of improving taxpayers' knowledge and understanding of the tax system as well as reviewing tax rates to increase tax compliance levels.